The relationship between stress and academic burnout in college students: evidence from longitudinal data on indirect effects - Zhang, Jun; Meng, Jiawen; Wen, Xin (Frontiers in Psychology, 2025)
ObjectiveThis study primarily examines the mechanisms through which stress affects academic burnout.MethodA total of 428 university students from three undergraduate institutions in China—Anhui Normal University, Tourism College of Zhejiang, and Bozhou University—were surveyed using the College Students' Stress Scale, the Academic Burnout Scale, the Social Support Scale, and the Self-Esteem Scale.ResultsThe results showed that stress significantly positively predicted academic burnout among college students and significantly negatively predicted their perceived social support. Both social support and self-esteem independently mediated the relationship between stress and academic burnout, and also served as a sequential (chain) mediator in this relationship.ConclusionStress can influence academic burnout both directly and indirectly. When individuals experience stress, their response to academic burnout is not only directly affected by the stress itself, but also indirectly influenced by two types of “psychological buffering resources”: internal resources (such as self-esteem) and external resources (such as social support). We refer to this phenomenon as the “Dual Buffering Path Model of Academic Burnout.” Based on these findings, it is necessary for educational authorities to take effective measures to reduce students' academic stress. In addition, friends, family, and teachers should offer emotional support, provide frequent positive feedback, and reinforce students' behaviors in order to foster their self-esteem and help them cope with academic burnout.